2023
DOI: 10.3390/plants12152847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Doses of Selenate, Selenite and Nano-Selenium on Biometrical Characteristics, Yield and Biofortification Levels of Vicia faba L. Cultivars

Anna Sindireva,
Nadezhda Golubkina,
Helene Bezuglova
et al.

Abstract: Faba bean (Vicia faba L.) has spread worldwide as an excellent source of proteins. To evaluate the efficiency of Se biofortification, four cultivars of V. faba (Belorussian, Russian Black, Hangdown Grünkernig, and Dreifach Weiβe) were foliar treated with 1.27 mM solutions of nano-Se, sodium selenate, and sodium selenite. Yield, protein, and Se contents were greatly affected by genetic factors and chemical form of Se. Selenium biofortification levels were negatively correlated with Se concentration in control p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…These results indicate a more toxic effect of selenite on wheat biomass when compared to selenate, where this effect is more pronounced in the roots. The results of this research are correlated with the results of research conducted by Hawrylak-Nowak et al [29], who noted a reduction in the biomass of shoots and roots of Cucumis sativus L. at 80 µM of selenate and 20 µM of selenite, but also with the results of other studies that concluded that selenite is a more toxic form than selenate [36,73,79]. Tian et al [80] emphasized that higher Se toxicity was associated with low S levels, during which the proportion of Se in proteins increases compared to S. From previous studies [80][81][82][83][84][85], it is evident that there was less S uptake in selenite treatments, which can cause and explain the higher selenite toxicity in wheat seedlings.…”
Section: Se Effect On Wheat Morpho-physiological Characteristicssupporting
confidence: 89%
“…These results indicate a more toxic effect of selenite on wheat biomass when compared to selenate, where this effect is more pronounced in the roots. The results of this research are correlated with the results of research conducted by Hawrylak-Nowak et al [29], who noted a reduction in the biomass of shoots and roots of Cucumis sativus L. at 80 µM of selenate and 20 µM of selenite, but also with the results of other studies that concluded that selenite is a more toxic form than selenate [36,73,79]. Tian et al [80] emphasized that higher Se toxicity was associated with low S levels, during which the proportion of Se in proteins increases compared to S. From previous studies [80][81][82][83][84][85], it is evident that there was less S uptake in selenite treatments, which can cause and explain the higher selenite toxicity in wheat seedlings.…”
Section: Se Effect On Wheat Morpho-physiological Characteristicssupporting
confidence: 89%
“…27 Furthermore, in contrast to selenate (SeO 4 2− ) and SeO 3 2− , Se ENMs have the effect of stimulating broad bean growth, seed weight and pod number. 28 Therefore, our results shows that Se ENMs can promote the accumulation of crop biomass, and the optimal treatment concentration of Se ENMs was 0.1 mg L −1 (Fig. 2b and c).…”
Section: Resultsmentioning
confidence: 57%
“…Many studies have confirmed the role of nano-Se in inducing the resistance of crops to phytopathogens such as Botrytis cinerea in cucumber [211], spot blotch disease in wheat [212], Podosphaera xanthii in melon [210], Fusarium-induced wilt disease in lettuce [209], and Alternaria leaf spot disease in the common bean [53]. Along with the mitigation of stress, other benefits that have been reported due to nano-Se in farming include nano-biofortification [204,205], improving the quality and shelf life of harvested crops [213], and mitigation of abiotic stresses, including salinity [214], heavy metals [215], and drought [216]. The beneficial role of nano-Se in animal production has been confirmed by many studies under traditional and stressful conditions [217,218].…”
Section: Seedling Productionmentioning
confidence: 93%
“…Nano-Se improved the seed weight, yield and quality, and biofortification level. [205] is Applied 50 and 100 ppm nano-Se and nano-Si Control Alternaria leaf spot disease Applied nano-Se and nano-Si was an effective alternative to fungicide against the studied phytopathogen.…”
Section: Biofortification Of Bean Seedsmentioning
confidence: 99%
See 1 more Smart Citation